2001
DOI: 10.3904/kjim.2001.16.2.110
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Parameters of Erythropoietin Hyporesponsiveness in Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: Background:The present study was aimed at investigating the predictive parameters of erythropoietin (epoetin) hyporesponsiveness in patients on continuous ambulatory peritoneal dialysis (CAPD).Methods:We studied 40 patients with end-stage renal disease who had been receiving CAPD for at least 6 months and epoetin therapy for at least more than 2 months. Pearson’s simple correlation and multiple stepwise linear regression analysis was used to discover what parameter can predict epoetin resistance. We expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
(35 reference statements)
3
10
3
Order By: Relevance
“…Similar results were reported from the European survey on anemia management [16]. Kim et al [8] reported that, in 40 continuous ambulant peritoneal dialysis (CAPD) patients, CRP was the most important predictor of EPO hypo-responsiveness. In our study, CRP levels in the group on an EPO dose !150 U/kg per week were significantly higher than those in the group on a dose <150 U/kg per week, and linear regression analysis showed a reverse relationship between ERI and CRP, which confirmed that CRP plays an important role in EPO resistance.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar results were reported from the European survey on anemia management [16]. Kim et al [8] reported that, in 40 continuous ambulant peritoneal dialysis (CAPD) patients, CRP was the most important predictor of EPO hypo-responsiveness. In our study, CRP levels in the group on an EPO dose !150 U/kg per week were significantly higher than those in the group on a dose <150 U/kg per week, and linear regression analysis showed a reverse relationship between ERI and CRP, which confirmed that CRP plays an important role in EPO resistance.…”
Section: Discussionsupporting
confidence: 74%
“…It was reported that serum albumin has a positive correlation with nPCR or the normalized protein equivalent of total nitrogen appearance (nPNA). Hypo-albuminemia, low nPCR (or nPNA) were indicators of both poor nutrition status and a predictive parameter of EPO hypo-responsiveness [2,8]. In our study we did not find any relationship between serum albumin and nPCR, but we did find that ERI had a negative correction with serum albumin and nPCR.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Nevertheless, it has been suggested that increased production of these cytokines may account for recombinant human erythropoietin (rhEpo) hypo-responsiveness. Therefore, reduction of infl ammatory cytokines can improve haematological status in advanced renal failure patients (Kim et al, 2001;Wei et al, 2007). In summary, these studies support the concept that silymarin antagonizes the action of pro-infl ammatory cytokines in treating infl ammatory anaemia in peritoneal dialysis patients.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have evaluated the role of various laboratory measures in predicting rHuEpo responsiveness, including albumin (25,26), CRP (25)(26)(27), ferritin (25,28), TSAT (25,27,28), and several dialysis adequacy indices (26,28). These studies support the notion that markers of inflammation such as an elevated CRP or reduced serum albumin tend to be associated with higher rHuEpo requirements, whereas greater iron stores and increased dialysis dose are associated with reduced rHuEpo needs.…”
Section: Discussionmentioning
confidence: 87%